2021
DOI: 10.1021/acs.biochem.1c00581
|View full text |Cite
|
Sign up to set email alerts
|

Heme-Edge Residues Modulate Signal Transduction within a Bifunctional Homo-Dimeric Sensor Protein

Abstract: Bifunctional enzymes, which contain two domains with opposing enzymatic activities, are widely distributed in bacteria, but the regulatory mechanism(s) that prevent futile cycling are still poorly understood. The recently described bifunctional enzyme, DcpG, exhibits unusual heme properties and is surprisingly able to differentially regulate its two cyclic dimeric guanosine monophosphate (c-di-GMP) metabolic domains in response to heme gaseous ligands. Mutagenesis of heme-edge residues was used to probe the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…In mechanistic terms, very minor differences in heme conformation with either O 2 or NO bound are translated into rather large conformational changes of DcpG, which result in dimerization of either the EAL domain or of the GGDEF domain, respectively. Based on structural and genetic evidence, single amino acids in close vicinity to the heme could be identified that play crucial roles in this interdomain signal transduction (Patterson et al 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…In mechanistic terms, very minor differences in heme conformation with either O 2 or NO bound are translated into rather large conformational changes of DcpG, which result in dimerization of either the EAL domain or of the GGDEF domain, respectively. Based on structural and genetic evidence, single amino acids in close vicinity to the heme could be identified that play crucial roles in this interdomain signal transduction (Patterson et al 2021b ).…”
Section: Introductionmentioning
confidence: 99%